2020
DOI: 10.1111/ajd.13456
|View full text |Cite
|
Sign up to set email alerts
|

How good is the Australian baseline series at detecting allergic contact dermatitis?

Abstract: Background Patch testing is the gold standard for the diagnosis of allergic contact dermatitis (ACD). The Australian Baseline Series (ABS) was formulated by our group to include the 60 most common and relevant allergens in our patient population. The aim of this study was to assess the efficacy of testing with the Australian Baseline Series in order to diagnose allergic contact dermatitis. Methods We conducted a retrospective study of 964 patients with ACD diagnosed at our centre from 1 January 2012 to 31 Dece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…As found in the Victorian study, fragrance allergens were frequently missed relevant reactions. 2 Fragrance allergy is not reliably detected by testing with the fragrance mixes. 8 Toluenesulfonamide formaldehyde resin, a cause of contact allergy to nail polish, was recently removed from the Letters to the Editors e79 ABS.…”
Section: Discussionmentioning
confidence: 99%
“…As found in the Victorian study, fragrance allergens were frequently missed relevant reactions. 2 Fragrance allergy is not reliably detected by testing with the fragrance mixes. 8 Toluenesulfonamide formaldehyde resin, a cause of contact allergy to nail polish, was recently removed from the Letters to the Editors e79 ABS.…”
Section: Discussionmentioning
confidence: 99%
“…A recent Australian paper showed that sensitivity to fragrances was frequently missed by the Australian baseline series, particularly for women 3 . Likewise, almost 10% of another study population had relevant reactions to individual fragrance allergens while being negative to fragrance mix I 8 .…”
Section: Discussionmentioning
confidence: 99%
“…A recent Australian paper showed that sensitivity to fragrances was frequently missed by the Australian baseline series, particularly for women. 3 Likewise, almost 10% of another study population had relevant reactions to individual fragrance allergens while being negative to fragrance mix I. 8 A Swedish study showed that 27% of patients who were positive to an individual allergen in fragrance mix I were negative to the fragrance mix I itself, while 36% demonstrated similar discordance when studying fragrance mix II.…”
Section: Fragrance Allergensmentioning
confidence: 99%
See 2 more Smart Citations